Thermally-induced structure evolution in ternary Ti1−xYxB2+Δ films. (15th April 2019) - Mikula, M.; Grančič, B.; Švec, P.; Roch, T.; Truchlý, M.; Kohuľák, O.; Satrapinskyy, L.; Fiantok, T.; Izaii, V.; Haršáni, M.; Orovčík, Ľ.; Kúš, P.
Abstract: Combining experiments and density functional theory, we investigate the effect of yttrium alloying on thermally-induced structure evolution and mechanical properties of TiB2+Δ . Ti0.78 Y0.22 B2.2 films consisting of TiYB2 filaments embedded in excess boron exhibit lower hardness of 31 GPa and significant reduction in elastic stiffness of 398 GPa in comparison with 38 GPa and 485 GPa, respectively, of reference TiB3.1 . Formation of the TiB2 and YB4 nano-sized grains as a result of spinodal decomposition of TiYB2 phase at 1200 °C is accompanied by a slight decrease in hardness to 28 GPa and further reduction of elastic stiffness to 383 GPa. Graphical abstract: Unlabelled Image